BAHAN AJAR MENULIS TEKS PROSEDUR BERBASIS KITAB SAFINATUN NAJAH DI LINGKUNGAN PESANTREN - Alivia Nadatul Aisyi; Arju Muti’ah; Bambang Edi Pornomo (Universitas Negeri Makassar, 2018)
Instructional Material Result in Writing a Procedure Text Based on Kitab “Safinatun Najah” in Pesantren. The research and development of this instructional material results in a product in the form of a procedure text module based on Safinatun Najah. This research and development model used the 4D model which is modified into define, design, and develop. The development of this instructional material was based on the 2013 Curriculum through the scientific approach. The result categorizes the module as a highly appropriate module with an average validity score of 91,7%. The implementation of the instructional material was conducted in two meetings. The results of the study obtained practical score of 95% and 98%. The response’s result toward the module obtained an average score of 89%. The result indicates that instructional material is appropriate to apply.